Visual C# 2005 demystified - Kent, Jeff (McGraw Hill, 2005)
Visual C# 2005 Demystified explains the language and its libraries and applications as well as how to use the integrated development environment. This self-teaching guide comes complete with key points, background information, quizzes at the end of each chapter, and even a final exam. Simple enough for beginners but challenging enough for advanced students, this is a lively and entertaining brush-up, introductory text, or classroom supplement.